Multivariate Partial Distribution: A New Method of Pricing Group Assets and Analyzing the Risk for Hedging - Feng Dai; Hui Liu; Ying Wang (Economics and Econometrics Research Institute (EERI), 2005)
Based on the Partial Distribution (Feng Dai, 2001), a new model to price an asset (MPA) is given. Going a step further, this paper puts forward the Multivariate Partial Distribution (MPD) for the first time. By use of MPD, we could gain a new kind of model for pricing the group assets (MPGA), in which the competition and cooperation are considered. Based on MPGA, the integrated risk of group assets can be divided to hedging risk and independent risk, and the corresponding models are given. So we could analyze the price risk of group assets in more particular way. The conclusions show that assets are hedged in simple way of one to one can not eliminates completely their market risk in many cases. So there should be an optimal ratio between underlying asset and its derivative in hedging. The approach to determine the optimal ratio in hedging is offered in this paper. By the MPA and MPGA, we also could interpret five of interesting economic propositions in analytic way.
Keywords: C1; C2; C3; C4; C5; C8; 330; Multivariate Partial Distribution pricing assets group assets risk analysis optimal hedging